Kulim (M) Berhad / Muhammad Afiqshakir Abdulshukor - Abdul Shukor, Muhammad Afiq Shakir (Faculty of Business and Management, 2023)
The Industrial Training Report is a story of my journey that I took on as an intern in Kulim (M) Berhad within 24 weeks. This report likely to show my industrial training process throughout the intern period which will include my industrial experiences such as engaging with many people, adaptations to working in real industry, gain knowledge and skills related and unrelated to work and personal development. I attended my first day of industrial training on 5th March 2023 and I was assigned under Mr. Mohd Shafiq Hariri Bin Mohd Khir, the senior executive and Person in Charge of OCP. During the 24 weeks period, I am working as an intern for sales and marketing team that hold the responsibility to find and penetrate the market to sell the products. Other than that, I also working as an intern for supply and management team that hold the responsibility to find crops suppliers and updating the stock offtake daily. The FarmByte was newly introduced and operated by Kulim (M) Berhad in 2023. This written report will include information about Kulim (M) Berhad and FarmByte regarding its background and activities that there has involved in. This Industrial Training Report will also consist of my profile, company’s profile, my training reflection, the SWOT analysis, discussion, recommendations and the conclusion of the written report. The company’s competitive position which are strength, weakness, opportunity and threat will be evaluate in the SWOT analysis. The SWOT analysis will discuss further about the performance of Farmbyte and will suggest the best recommendation to the company for further improvement.